DETERMINATION OF FRACTAL REACTION DIMENSION IN DISSOLUTION STUDIES - Valsami, G.; Macheras, P. (EUROPEAN JOURNAL OF PHARMACEUTICAL SCIENCES, 1995)
The paper presents a method for the calculation of fractal reaction dimension, D-R, in dissolution studies of powdered substances with a given particle size distribution. An estimate for D-R can be directly obtained from dissolution experiments using the well known Hixson-Crowell equations in a modified form. The estimation is accomplished with a special computer program in BASIC which was developed and applied to simulated errorless and contaminated data with very good results. A practical demonstration of the method's usefulness was shown on experimental data taken from the literature.
Keywords: Dissolution; fractal; FRACTAL DIMENSION; FRACTAL REACTION DIMENSION